2021
DOI: 10.4103/ojo.ojo_87_21
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of webinars during the COVID.19 pandemic: A survey of ophthalmology trainees from India

Abstract: OBJECTIVE: The objective of the study was to assess the perceived utility and the impact of web-based teaching programs being conducted following the COVID-19 pandemic. METHODS: An online survey was sent to trainee ophthalmologists across India through various social media platforms. The responses were tabulated and analyzed. RESULTS: A total of 768 valid responses were recorded. Majority of respondents (52.2%) felt that the ideal duration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…Another cross-sectional study conducted in India, assessing the impact of the webinars on the residents’ learning during the pandemic, revealed that 75% of residents positively graded webinars as a good/very good academic tool and nearly 77% of them admitted that they gained substantial knowledge of the topic in question [ 28 ]. The positive perception and usefulness of webinars in enhancing theoretical knowledge and practical skills were also confirmed in another survey study among Indian ophthalmology residents conducted by Mishra et al [ 13 , 17 ]. They revealed that 74% of residents preferred webinars based on their residency curriculum with clinical problem-solving as the specific area of interest (40.9%) and the ideal duration of webinars between 60 and 120 min [ 13 ].…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Another cross-sectional study conducted in India, assessing the impact of the webinars on the residents’ learning during the pandemic, revealed that 75% of residents positively graded webinars as a good/very good academic tool and nearly 77% of them admitted that they gained substantial knowledge of the topic in question [ 28 ]. The positive perception and usefulness of webinars in enhancing theoretical knowledge and practical skills were also confirmed in another survey study among Indian ophthalmology residents conducted by Mishra et al [ 13 , 17 ]. They revealed that 74% of residents preferred webinars based on their residency curriculum with clinical problem-solving as the specific area of interest (40.9%) and the ideal duration of webinars between 60 and 120 min [ 13 ].…”
Section: Resultsmentioning
confidence: 52%
“…Wang et al [ 35 ] also found that up-to-date and accurate health information (e.g., treatment, local outbreak situation) and precautionary measures (e.g., hand hygiene, wearing a mask) were associated with a lower psychological impact and lower stress, anxiety, and depression in the general Chinese population. Consistent with these findings, a study conducted by Mishra et al [ 17 ], wherein stress levels among participants were significant, showed that approximately 65% of those who were on COVID-19 duties felt that the PPE they were using was inadequate. In contrast, most surveyed trainees in Saudi Arabia experienced depressive symptoms, which were noted in over half of them, but were provided with adequate PPE, built-in shields for slit lamps, and updated protocols on how to limit SARS-CoV-2 transmission [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations